Stability of equine IgG antivenoms obtained by caprylic acid precipitation: Towards a liquid formulation stable at tropical room temperature - Segura Ruiz, Álvaro (2009)
Liquid formulations of antivenom require a cold chain for their distribution and storage, especially in tropical countries characterized by high temperature and humidity (climatic zone IV). Since cold chain is often deficient in many regions, there is a need to develop novel formulations of liquid antivenoms of higher stability at room temperatures. The effect of addition of the polyols mannitol and sorbitol on the thermal stability of caprylic acid-fractionated equine whole IgG antivenoms was assessed in preparations having different concentrations of protein and phenol. Results evidenced that: (1) turbidity increases proportionally to phenol and protein concentration. (2) After one year of storage at 25 °C, caprylic acid-purified antivenoms, formulated with or without polyols, did not show evidences of instability. (3) Formulation of antivenoms with 2.0 M sorbitol prevents the appearance of turbidity after one year storage at 37 °C; however, there was a partial loss in neutralizing potency in these conditions. Results suggest that formulation based on sorbitol is an option to obtain liquid whole IgG antivenoms of higher stability at tropical room temperatures.